Effects of prenatal stress on motor performance and anxiety behavior in Swiss mice - Pallares, Maria Eugenia (2007)
Stressor presence during the last weeks of gestation has been associated with behavioral disorders in later life. In this study we support further research on the long term effects of prenatal stress on Swiss mice descendant´s behavior. Prenatal stress procedure consisted on restraining the dams under bright light for 45 min, three times per day from the 15th day of pregnancy, until birth. After weaning, offspring´s motor performance and spontaneous exploratory behavior were measured by the tight-rope and T-maze tests, respectively. We also evaluated anxiety behavior using elevated plus maze test. We found that maternal stress improves the performance of the animals in the tight rope test and that this effect was sex and age dependent: prenatal stressed males obtained the best scores during the first month of life, while in females the same was achieved at the second month. Spontaneous exploratory behavior analysis revealed that it was elevated in prenatal stressed males and that this effect persisted on time. However, we did not find significant differences on this behavioral response among both females groups. Finally, differences on anxiety behavior were found only in females: prenatally stressed animals showed a higher proportion of entries into the open arms of a plus maze (reduced anxiety) compared to the control group. Our results show that prenatal stress modifies the normal behavior of the progeny: prenatal stressed animals have a better performance in the carried out test. These notably results suggest the existence of an adaptive response to prenatal stress.